Playing for keeps : a novel - Bellefleur, Alexandria (Avon, 2026)
"Poppy Peterson's life is finally back on track and she's thriving as the publicist of the NFL's most promising quarterback (and her childhood best friend), Cash Curran. So, she doesn't appreciate when he makes an impulsive and public pass at America's popstar darling, Lyric Adair. When Lyric's notorious publicist Rosaline Sinclair reaches out, Poppy is ready to face her wrath, but instead learns that Lyric is equally interested. As Cash and Lyric embark on their ill-advised whirlwind romance, Poppy and Rosaline are forced together, each determined to protect their own client from the other. Poppy is frustrated by Rosaline's cool demeanor, while at the same time, as a legend in the industry, she's determined to impress her. But, no matter what she does, she can't shake the feeling that Rosaline doesn't like her. That is until one steamy night, when the two women contend with their unexpected feelings and begin a messy romance of their own. But with paparazzi, tabloids, and stalker fans nipping at their heels, Poppy and Rosaline's loyalties will be tested in ways they could never expect." --